النفط والقضية الكردية في العهد الملكي (1921- 1932) - غفور, دارا جمال (Sulaimani Journal for Humanities, 2023)
The discovery and extraction of oil in commercial quantities from the northern region had a great impact on determining the reality and future of contemporary Iraq, given the strategic importance of oil to the British political decision-maker who controlled Iraq’s capabilities during the monarchy, which made the northern region of Iraq enter into the circle of corporate equality. The global oil resources of the colonial countries, therefore, oil was the main element that controls the determination of the future of this region during the mandate and royal era that Iraq passed through. We divided the research into two Chapters: The First Chapters: A historical overview of the discovery of oil and the colonial struggle over northern oil, we divided it into two sections, First section: A historical overview of oil discovery and oil extraction in northern Iraq, Second section: The colonial struggle over northern oil during the British mandate over Iraq. As for the Second Chapter: Colonial competition, the establishment of oil companies, and its impact on demographics, we divided this into two sections, First section: Colonial competition and the establishment of the Mosul Oil Company during the royal era. As for the second section: The impact of oil on the demographic structure of the northern region.
Keywords: oil; the Kurds; the royal era; Mosul; Kirkuk